A domain-specific peer-review checklist for sport science journals: Translating a conceptual framework into practice - Spyridon Plakias (CV Rezki Media, 2026)
The peer-review process plays a central role in ensuring the quality and credibility of scientific research; however, it remains characterized by variability, limited standardization, and a lack of domain-specific evaluation criteria. These limitations are particularly evident in sport science, a multidisciplinary field involving complex, context-dependent, and applied performance data. Although several guidelines for peer-review exist, they are often either generic or tailored to specific domains, limiting their applicability to sport science research. The aim of the present study was to develop a comprehensive, domain-specific reviewer checklist for sport science journals. Building on a previously proposed conceptual framework of publishable research, the checklist operationalizes key dimensions of manuscript evaluation into structured criteria, spanning editorial screening, conceptual foundation, methodological and analytical rigor, research transparency, scientific communication, and scientific and practical impact. In addition, the framework integrates both hierarchical and iterative elements of the peer-review process, conceptualizing manuscript evaluation as a cyclical process that begins and concludes with editorial decision-making. The proposed checklist provides a structured and contextually relevant tool to support reviewers in conducting more consistent and transparent evaluations, while assisting editors in decision-making and offering authors clearer expectations. Although not yet empirically validated, the proposed framework represents a step toward improving the quality, consistency, and contextual relevance of peer-review in sport science.